Safety and health in construction (ILO GenevaCH)
Reviews developments in the construction industry, its special characteristics that distinguish it from other manufacturing industries. Gives examples of law and practice of member states with regards to construction. Includes questionnaire to governments and the texts of the Safety Provisions (Building) Convention, 1937 (No.62) Recommendation (No.53) and other ILO instruments dealing with the protection of workers from safety and health hazards.
Report IV {2A, 2B}